Averting Repulsion? Body-Directed Self-Disgust and Autobiographical Memory Retrieval. Issue 1 (7th February 2022) - von Spreckelsen, Paula; Wessel, Ineke; Glashouwer, Klaske A.; de Jong, Peter J.
A negative body image and appraisals of disgust with one's (physical) self reflect schematic representations of one's body, which we classified under the term repulsive body image (RBI). We propose that an RBI biases autobiographical memory processing towards schema (=RBI)-congruent and over-general memories. Women with high (HRBI ; n = 61) and low (LRBI ; n = 64) levels of habitual body-directed self-disgust were asked to retrieve memories in response to abstract body words in a minimal instruction Autobiographical Memory Test. Compared to the LRBI group, the HRBI group recalled a higher number of autobiographical memories that involved appraisals of the own body as disgusting, and reported elevated habitual tendencies to prevent experiencing disgust towards the own body. Neither RBI scores nor tendencies to prevent experiencing body-related disgust were found to be statistically significant predictors of memory specificity. The overall low memory specificity could be indicative of a need for more sensitive measures of autobiographical memory specificity to examine disgust-driven avoidance at the memory level. Nevertheless, the current results may indicate that disgust-related memories and the prevention of experiencing disgust towards the own body could play a role in body image concerns.